A perspective on the activation energy dependence of the Fischer-Tropsch synthesis reaction mechanism. (16th January 2023) - Okonye, Leonard U.; Yao, Yali; Ren, Jianwei; Liu, Xinying; Hildebrandt, Diane
Graphical abstract: Highlights: Fischer-Tropsch synthesis was studied at 160–260 °C with Ru/mesoCo3 O4 and Ru/SBA-15. Graphing the conversion to obtain the activation energy and kinetic regimes. Multi-slope Arrhenius plots obtained in this work are split into temperature ranges. Different activation energies (Ea ) deduced from the Arrhenius equation. Different activation energies (Ea) were ascribed to different reaction mechanisms. CO dissociation and CO insertion mechanisms may occur at different temperatures. Transition temperature is where a separate mechanism takes over. Abstract: The conversion of syngas to hydrocarbons is achieved through different mechanisms based on the type of perceived monomer and chain initiator, with preference given to two key mechanisms in the explanation of the conversion process. Concerted efforts at explaining the Fischer-Tropsch Synthesis (FTS) mechanism remain unresolved. By graphing the energy of a reaction using the Arrhenius equation, changes occurring in a reaction for temperature variation can produce valuable information on the reaction. This work uses the activation energy (Ea ) deduced from the Arrhenius equation to determine the coexistence nature of the different mechanisms for the FTS reaction. The work shows the reaction mechanisms are not competing, but rather complement one another during FTS reaction to yield different products.